Research is born free and everywhere is in chains : How the evolution of open access can contribute to developing a more democratic approach for science - Terry, Robert Fraser (Septentrio Conference Series, 2019)
Watch the VIDEO. The open access movement has come a long way since its origins at the end of the 1990s but we still haven’t achieved the tipping point to make the open access approach, the normal approach. Why are initiatives such as Plan S needed and why did the World Health Organization feel it necessary to join? This talk will draw on experiences at Wellcome Trust and WHO, implementing the first open access policy for a European Research funder, creating Europe PubMed Central and developing a policy that works for a United Nations agency. Robert will outline why achieving open access requires addressing barriers across political, technical and cultural barriers – with perhaps the culture of research assessment and reward needing the biggest change if we are to truly democratise science so that the people who pay for the research, the taxpayers, can access, read and use the research.